Optical properties enhancement via WSSe/silicene solar cell junctions - Pedrosa, Renan Narciso; Villegas, Cesar E. P.; Rocha, A. R. [UNESP]; Amorim, Rodrigo G.; Scopel, Wanderlã L. (Royal Society of Chemistry (RSC), 2024)
2D Janus monolayers exhibit nanoscale asymmetric surface organization along the out-of-plane direction and have recently emerged as a class of 2D materials. In this work, we investigate the energetic, electronic, and optical properties of the vertical van der Waals stack between WSSe and silicene monolayers based on first-principles calculations. The Janus/silicene interface formation is driven by an exothermic process, and charge transfer from the silicene to the Janus monolayer is observed. The intrinsic properties of silicene and Janus are preserved despite the stacking of the parts. The Bethe-Salpeter equation (BSE) was used to understand the contact influence on the optical absorption spectrum of the vertical interface. Our findings reveal that the power conversion energy (PCE) of the heterostructure is boosted 2.42 times higher than that of the Janus monolayer. Thus, due to its PCE and transparent electrical contact, the heterojunction is a promising candidate for use as a photovoltaic device compared to its counterparts.